2020
DOI: 10.1016/j.celrep.2020.107939
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Adaptation of Ultra-small Parasitic Reduced Genome Bacteria to Mammalian Hosts

Abstract: SUMMARY The first cultivated representative of the enigmatic phylum Saccharibacteria (formerly TM7) was isolated from humans and revealed an ultra-small cell size (200–300 nm), a reduced genome with limited biosynthetic capabilities, and a unique parasitic lifestyle. TM7x was the only cultivated member of the candidate phyla radiation (CPR), estimated to encompass 26% of the domain Bacteria. Here we report on divergent genomes from major lineages across the Saccharibacteria phylum in humans and mamm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 62 publications
9
133
0
Order By: Relevance
“…Comparative genomics revealed both cell surface and intracellular proteins that are differentially enriched in susceptible vs. resistant and permissive vs. nonpermissive strains ( Table 1). Our previous transcriptomic analysis and recent study based on predicted metabolic complementarity between TM7x and XH001 similarly identified the importance of cell surface and cell wall components in the TM7x/ XH001 relationship [38,55]. Consistent with this idea, our analysis showed that most of the groups were enriched with different cell wall modifying genes at the carbohydrate and peptidoglycan modules (Table 1).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Comparative genomics revealed both cell surface and intracellular proteins that are differentially enriched in susceptible vs. resistant and permissive vs. nonpermissive strains ( Table 1). Our previous transcriptomic analysis and recent study based on predicted metabolic complementarity between TM7x and XH001 similarly identified the importance of cell surface and cell wall components in the TM7x/ XH001 relationship [38,55]. Consistent with this idea, our analysis showed that most of the groups were enriched with different cell wall modifying genes at the carbohydrate and peptidoglycan modules (Table 1).…”
Section: Discussionsupporting
confidence: 84%
“…Further, the relationships between Saccharibacteria and Actinobacteria in their native oral habitats require direct investigation. While microscopy confirms the epibiotic association is conserved [ 32 , 55 , 56 ], the potentially diverse in situ interactions could significantly alter the host/symbiont relationships. As the majority of the diverse and ubiquitous CPR phyla are thought to engage in similarly obligate symbioses [ 63 , 64 ], the extent of host range for CPR organisms could have tremendous impact on our understanding of the role such bacteria/bacteria associations play in their respective environments, from the oral microbiome to aquatic and terrestrial habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Portnoybacteria bacterium BS750m-G76. These proteins were unique for these microbes in the entire euxinic waters, which suggests a parasitic lifestyle from which these Patescibacteria could translocate nutrients, proteins, and DNA from or to a putative host [22].…”
Section: Resultsmentioning
confidence: 99%
“…16S rRNA gene sequencing revealed several samples with enriched growth of Saccharibacteria phylum G3 group member HMT‐351, provisionally named “Ca. Nanosyncoccus nanoralicus” (McLean et al., 2018, 2020), that is likely an epibiont parasite on a bacterial host similar to strain TM7x (He et al., 2015). To identify the potential host of this bacterium, samples were divided into a group of biofilms with G3 HMT‐351 present and a group with G3 HMT‐351 absent, and the relative abundance of each species was averaged within each group.…”
Section: Methodsmentioning
confidence: 99%